Pengetahuan Manajemen, Kompensasi, Motivasi Kerja Dalam Meningkatkan Kinerja Karyawan Dengan Semangat Kerja Sebagai Variabel Intervening - I Kadek Rahyudi Sukarta; Ni Putu Nina Eka Lestari (Universitas Pendidikan Nasional, 2019)
ABSTRACTHuman resources (HR) is an important role for an organization that fails to achieve its goals. Therefore HR needs to get knowledge management, compensation, work motivation and have a good working spirit. Humans as the key to the success of a company desperately need knowledge of good management in order to manage the company. Employees need knowledge about management to provide knowledge to organizations within a company. There are 2 (two) types of knowledge, namely tacit knowledge and explicit knowledge. Then compensation is very influencing employee performance because with compensation, employees will also get a service reward that is appropriate and motivates employees. Work motivation can be interpreted as a condition in one's personal self so that the person is motivated to carry out an activity or activity and has a work spirit to improve optimal performance within the company. This study uses CB-SEM (Covariance Based-Structural Equation Modeling) analysis techniques. Besides that, the sobel test testing method was also used in this study. The data used in this study are primary data through the distribution of questionnaires and secondary data from previous studies, literature, print media (newspapers and magazines) and electronic media (internet).The results showed that management knowledge, compensation, work motivation, and work morale had a positive and significant influence on employee performance at Danoya Villa Batu Belig, Krobokan. (1) The value of t count = 2.2933> of the value of t table = 1.96. Thus it can be said that the Work Spirit variable is the mediating variable of the influence of Management Knowledge on Employee Performance. (2) Value of t count = 1.5606 <from the value of t table = 1.96. Thus it can be said that the Work Spirit variable is not the mediating variable of the influence of Compensation on Employee Performance. (3) Value of t arithmetic = 1.6767 <from ttable = 1.96. Thus it can be said that the Work Spirit variable is not a mediating variable the effect of Work Motivation on Employee Performance. Based on the results of the study it can be suggested as follows: Villa Danoya Batubelig Kerobokan Badung in fostering employee morale and performance in order to better understand what the employees want and need. For this reason, the Villa Danoya Batubelig Kerobokan Badung is intended to further enhance the development of human resources in the company. With the growth of morale and employee performance, it will have an impact on improving services, so that the number of guests staying overnight will increase